1995
DOI: 10.1097/00001888-199504000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of student and preceptor gender on clinical grades in an ambulatory care clerkship

Abstract: The female students received higher clinical grades in the ambulatory care clerkship, especially when the preceptor was male. Perhaps gender interaction should be considered when assigning students to preceptors and evaluating grading practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 0 publications
1
14
1
Order By: Relevance
“…Conversely, evaluation of clinical performance of final‐year students on core equine and small animal rotations suggested that male students performed slightly better. This observation contrasts with findings in medical education, where no gender effect was observed or where female clinical performance was higher . This may reflect a gender bias based on smaller numbers of male students in veterinary cohorts or may be indicative of inherent difficulties with assessing clinical performance.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Conversely, evaluation of clinical performance of final‐year students on core equine and small animal rotations suggested that male students performed slightly better. This observation contrasts with findings in medical education, where no gender effect was observed or where female clinical performance was higher . This may reflect a gender bias based on smaller numbers of male students in veterinary cohorts or may be indicative of inherent difficulties with assessing clinical performance.…”
Section: Discussioncontrasting
confidence: 91%
“…This observation contrasts with findings in medical education, where no gender effect was observed or where female clinical performance was higher. 23,24 This may reflect a gender bias based on smaller numbers of male students in veterinary cohorts or may be indicative of inherent difficulties with assessing clinical performance. In the current study, data from only the two compulsory internal (on campus) rotations were included, as rotations at different distributed practices or based on different elective choices were considered to possibly introduce greater heterogeneity into the data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in teaching perceptions related to resident gender are more difficult to explain. Gender differences have been found in medical school grading and in numerical scores from the American Board of Internal Medicine evaluation forms 13–15 . Additionally, differences in teaching related to the gender composition of the teacher‐student pair have been found during ambulatory patient encounters 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Female medical students in Ireland were more likely to achieve honours, especially in paediatrics, psychiatry and obstetrics and gynaecology 57 . US women achieved higher clinical grades in ambulatory care and surgical clerkships 58,59 . However, most such gender differences in medical school performance are so small (in terms of differences in marks) that they are of little practical importance.…”
Section: Culture and Practice Of Medicinementioning
confidence: 99%
“…57 US women achieved higher clinical grades in ambulatory care and surgical clerkships. 58,59 However, most such gender differences in medical school performance are so small (in terms of differences in marks) that they are of little practical importance. These results come from large-scale study designs, so small differences in means give statistically significant results.…”
Section: Differential Academic Performancementioning
confidence: 99%